(untitled) (Damu Journal of Sport Sciences, 2025)
Mastery learning using the peer teaching strategy is one of the modern strategies that takes into account individual differences in learners' experiences and abilities without compromising the educational and academic level and competence of the learning process. Sometimes, it may require segmenting the movements and skills to be mastered, as their complexity requires segmentation. There are other skills that need to be taught as a single unit without segmentation or dividing the group into smaller groups. This is in addition to bringing the learner group to a level of mastery. Herein lies the importance of the research in using mastery learning according to the peer teaching strategy to understand its impact on learning and mastering basic skills for intermediate-level female students. The research aims to identify the impact of mastery learning according to the peer teaching strategy on learning some basic handball skills for intermediate-level female students. The researcher used the experimental method, using a pre-test and post-test method for equal groups. The researcher concluded: 1. There was positive development for the experimental and control groups in learning the skill of passing from head level, the skill of scoring from a standing position, and tapping in handball. 2. The experimental group, which used mastery learning according to the peer teaching strategy, outperformed the control group in learning the skill of passing from head level, the skill of scoring from a standing position, and tapping in the post-tests. 3. The use of mastery learning according to the peer teaching strategy played an important and fundamental role in increasing interaction between students and increasing their desire and motivation to rely on themselves, especially in the main section of skills.